Challenges and considerations in implementing Chilean law 21.057: Video-recorded interviews for child and adolescent victims - Olate Cisternas, Paola (Revista de Estudios de la Justicia, 2024)
This article analyzes the challenges and design considerations involved in the implementation of public policy through the enactment of Law 21.057. This law regulates recorded video interviews and other protective measures for minors who are victims of sexual and violent crimes. Planned for a gradual three-stage rollout in Chile law aims to prevent secondary victimization of children and adolescents. It functions as a differentiated state policy for this age group, ensuring their access to the criminal process with protection and without infringing on their rights, while considering their developmental stage. The methodology employed an exhaustive literature review and consultation with experts in the field. The analysis focuses on law’s effectiveness, considering the factors legislature took into account to achieve its objectives. They include identifying facilitators or obstacles that might impact the law’s declared purpose of preventing the double victimization of children and adolescents during their involvement in the criminal justice system. By examining those factors, the article aims to assess the success of this public policy and potentially propose modifications to address shortcomings or prevent issues that could lead to its failure.